Strategies for enhancing home-based cardiac rehabilitation self-management for patients with coronary heart disease: a qualitative study - Zhen Yang; Xutong Zheng; Yu Gao; Chunqi Zhang; Aiping Wang (BMC Nursing)
Abstract Background Self-management is regarded as a crucial factor influencing the effectiveness of home-based cardiac rehabilitation for patients with coronary heart disease. In nursing practice, nurses employ a variety of strategies to enhance self-management of patients. However, there exists a disparity in nurses’ perceptions and practical experiences with these strategies. This study aimed to explore the experiences and strategies of clinical nurses in enhancing home-based cardiac rehabilitation self-management for patients with coronary heart disease. Methods A descriptive qualitative study was conducted across two large cardiac rehabilitation centers. Clinical nurses were selected using purposive sampling with maximum variation strategies. Semi-structured interviews were conducted to capture nurses’ experiences and strategies for enhancing home-based cardiac rehabilitation self-management. Content analysis was utilized to analyze the textual data. Results A total of 18 eligible clinical nurses participated in this study. The interviews resulted in the extraction of seven subthemes, which were consolidated into three main themes: (1) Personalized and Engaging Educational Approaches, including Precision Education–Tailored, Adaptive Approaches and Visual Aided Education–Beyond Simplification to Deep Engagement; (2) Contextual and Psychologically Grounded Nudging Strategies, comprising Information Framing–Psychological Leveraging for Informed Choices, Social Norms–Leveraging Peer Influence for Motivation, and Verbal Reminders–The Power of Consistency and Reinforcement; (3) Continuous and Personalized Support Systems, involving Regular Follow-Up–Dynamic Support for Ongoing Engagement and Collaborative Management–Building a Team for Long-Term Success. These robust strategies can effectively enhance self-management behaviors and quality of life in patients undergoing home-based cardiac rehabilitation. Conclusions From the perspective of clinical nurses, this study explored a variety of strategies for improving home-based cardiac rehabilitation self-management in patients with coronary heart disease. This provides theoretical support for optimizing intervention measures and promotes the effective delivery and application of self-management strategies in practice. Clinical trial number Not applicable.